IMPROVEMENT OF ACCOUNTING AND ACCOUNTING OF LOCAL BUDGET REVENUES (European Journal of Pedagogical Initiatives and Educational Practices, 2024)
The prudent management of local budget revenues is a cornerstone of effective fiscal governance, as it enables local governments to allocate resources efficiently, promote economic growth, and deliver essential public services. However, the accounting and accounting of local budget revenues often present a complex challenge, particularly in developing countries where limited resources and inadequate institutional capacity can hinder the accuracy and reliability of financial reporting. In this article, we will examine the importance of improving accounting and accounting of local budget revenues, and discuss the key strategies and best practices that can be employed to achieve this objective.